CENTROID-MOMENT TENSOR SOLUTIONS FOR OCTOBER-DECEMBER 1986 - Dziewonski, A; Ekstrom, G; Woodhouse, J; Zwart, G (1987)
Centroid-moment tensor solutions are presented for 189 earthquakes that occurred during the fourth quarter of 1986. The solutions are obtained using corrections for aspherical Earth structure. © 1987.